Poor Renal Outcome of Antineutrophil Cytoplasmic Antibody Negative Pauci-immune Glomerulonephritis in Taiwanese - Peir-Haur Hung (Journal of the Formosan Medical Association, 2006)
Pauci-immune glomerulonephritis (GN) is an important cause of crescentic GN, acute renal failure and mortality. However, data are limited on the clinical presentation and outcome in antineutrophil cytoplasmic antibody (ANCA) negative patients, especially in Asians. Methods: This retrospective study analyzed medical records and pathology slides of patients who received renal biopsy between February 1998 and October 2004. Enzyme-linked immunosorbent assay was used routinely for ANCA testing in all patients. Results: Among 637 patients with biopsy-proven GN included in this study, 88 (13.8%) had glomerular crescent formation. Among them, pauci-immune crescentic glomerulonephritis (PICGN) (42 patients, 47.2%) and lupus nephritis (25 patients, 28.4%) were the most common pathologic diagnoses. Lupus patients were younger (p = 0.028), while PICGN patients had more chronic lesions (p< 0.001), extensive glomerular crescents (p< 0.001), less severe proteinuria (p< 0.001) and poorer renal survival (p= 0.0017). Among the PICGN patients, 62.5% had a positive ANCA test, 80% had myeloperoxidase-ANCA and 20% had proteinase-3-ANCA. Subgroup analysis showed that ANCA negativity was associated with less crescent formation (p<0.001) but more chronic glomerular lesions (p<0.001) and a trend toward worse renal outcome (p =0.055). Conclusion: This study illustrates the necessity for pathologic diagnosis of pauci-immune GN despite ANCA negativity. The poor prognosis associated with ANCA negativity in this study may be partly due to delayed diagnosis since these patients frequently lacked systemic involvement.